A single-center observational study on the efficacy of percutaneous coronary intervention for ischemic heart failure: A cohort study. Issue 13 (March 2018) - Wang, Zongtao; Jin, Lijun; Zhou, Wanxing; Lei, Da; Yan, Hong; Yu, Huimin; Zeng, Zhihuan; Zhu, Guiping; Zheng, Jianyi; Dai, Yining; Wang, Haifang
Abstract : Abstract: The effects of revascularization by percutaneous coronary intervention (PCI) on cardiac function and clinical outcomes in patients with confirmed coronary artery disease (CAD) and heart failure (HF), on the basis of the optimal medical treatment recommended by current guidelines, remain to be determined. A cohort study was performed to evaluate the efficacy of PCI on the basis of optimal medical treatment in patients with CAD and HF. Patients who received PCI were subsequently grouped according to partial and complete revascularization (CR) depending on the PCI outcome. The primary outcome was defined as a composite outcome of major adverse cardiovascular events (MACEs). Changes in left ventricular ejection fraction (LVEF) also were compared. A total of 69 patients (12 who received medical treatment and 57 who received PCI) were included. Patients in the PCI group showed significantly improved LVEF ( P < .001), but patients in the medical treatment group did not ( P > .05) after 3 months of follow-up. MACEs occurred in 50% patients in the medical treatment group and 19.3% patients of the PCI group, with this difference almost reaching statistical significance ( P = .06). Compared with patients who received medical therapy only, patients who received PCI experienced better survival ( P = .02). Moreover, survival seemed to be better in patients who achieved CR with PCI of the coronary arteries than in those who had partial revascularization of the coronary arteries ( P = .06). PCI may be effective for improving survival in patients with CAD and HF.